Foundations of Bioethics and Biosafety: Educational manual for independent work of students of the 1-st course of II International Faculty - Sepetyi, D.; Сепетий, Дмитро Петрович (Запорізький державний медичний університет, 2020)
The manual contains themes, glossary, plans, reviews of the themes, control questions and tasks for independent work in the discipline Foundations of Bioethics and Biosafety. For the students of the 1-st course of II International Faculty.